2018
DOI: 10.1093/sleep/zsy086
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and genetic features of sleep ontogeny in Drosophila

Abstract: The fruit fly Drosophila melanogaster, like most organisms, exhibits increased sleep amount and depth in young compared to mature animals. While the fly has emerged as a powerful model for studying sleep during development, qualitative behavioral features of sleep ontogeny and its genetic control are poorly understood. Here we find that, in addition to increased sleep time and intensity, young flies sleep with less place preference than mature adults, and, like mammals, exhibit more motor twitches during sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 48 publications
6
20
0
Order By: Relevance
“…More broadly, there are no known genes that regulate sleep ontogenetic change. We previously found that all studied short and long-sleeping Drosophila mutants sleep more when young (Dilley et al, 2018). Thus, genes regulating sleep ontogenetic change are likely distinct from 50 those that control sleep duration.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…More broadly, there are no known genes that regulate sleep ontogenetic change. We previously found that all studied short and long-sleeping Drosophila mutants sleep more when young (Dilley et al, 2018). Thus, genes regulating sleep ontogenetic change are likely distinct from 50 those that control sleep duration.…”
Section: Introductionmentioning
confidence: 95%
“…Across species, sleep amounts are highest in early life and decrease as animals mature (Kayser and Biron, 2016;Roffwarg et al, 1966). Increasing evidence suggests early life sleep may represent a distinct behavioral state, uniquely evolved for the needs of a developing nervous system (Blumberg, 2015;Clawson et al, 2016;Dilley et al, 2018;35 Frank, 2011). In humans, childhood sleep disturbances portend later neurocognitive deficits, possibly because sleep loss impinges on neural circuit formation (Kotagal, 2015;O'Brien, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across species, sleep amounts are highest in early life and decrease as animals mature (Kayser and Biron, 2016;Roffwarg et al, 1966). Increasing evidence suggests early life sleep may represent a distinct behavioral state, uniquely evolved for the needs of a developing nervous system (Blumberg, 2015;Clawson et al, 2016;Dilley et al, 2018;Frank, 2011). In humans, childhood sleep disturbances portend later neurocognitive deficits, possibly because sleep loss impinges on neural circuit formation (Kotagal, 2015;O'Brien, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Like other animals, the fruit fly, Drosophila melanogaster, exhibits increased sleep duration in young adulthood that tapers with maturity (Dilley et al, 2018;Kayser et al, 2014;Shaw et al, 2000). At the circuit level, activity of wake-promoting dopaminergic (DA) neurons increases as flies mature, exerting greater inhibitory influence on the sleep-promoting dorsal fan shaped body (dFSB) (Donlea et al, 2014;Kayser et al, 2014;Liu et al, 2012;Ueno et al, 2012).…”
Section: Introductionmentioning
confidence: 99%